The FORMNET‐B database: monitoring the biomass and dynamics of disturbed and degraded tropical forests. (5th July 2013) - Cho, Percival; Blackburn, George A.; Bird, Neil M.; Brewer, Steven W.; Barlow, Jos; Wilson, Bastow
Abstract The biomass and dynamics of disturbed and degraded tropical forests have mostly been ignored in the recent scientific literature, partly because of a spotlight on old‐growth forests but also due to a lack of long‐term data from degraded forests. There is a pressing need to understand the rates and patterns of growth, mortality and recruitment in degraded forests, not only because they are increasing in area relative to old‐growth forests, but also due to their potential capacity to sequester large amounts of carbon dioxide from the atmosphere. This paper introduces a permanent forest plot network and database, FORMNET‐B (GIVD ID# NA‐BZ‐001), designed to study the long‐term dynamics of disturbed and degraded tropical forests in Belize, Central America.